Spanish Translation and Validation of the COVID Stress Scales in Peru - Noe-Grijalva, Martin; Polo-Ambrocio, Anali; Gómez-Bedia, Karla; Caycho-Rodríguez, Tomás (Frontiers in Psychology, 2022)
The objective of the study was to translate and validate the COVID Stress Scales (CSS-36) into Spanish in Peru. 1424 people, selected through a non-probabilistic sampling, participated in the study. Factor analysis confirmed an initial six-dimensional factorial structure of the CSS-36. Reliability by internal consistency was good for the dimensions of fear of danger, socioeconomic consequences, xenophobia, fear of contamination, traumatic stress and compulsive control. In addition, the factorial structure of scale has been shown be strictly invariant for both males and females. The Spanish version of the CSS-36 has evidence of validity, reliability and invariance to measure COVID-19 stress in a Peruvian sample.